Angiotensin converting enzyme inhibitor captopril prevents neuronal overexpression of amyloid-beta and alpha-synuclein in Drosophila melanogaster genetic models of neurodegenerative diseases (Nigerian Journal of Physiological Sciences, 2022)
Background: Parkinson disease (PD) and Alzheimer’s disease (AD) are progressive neurodegenerative disorders characterized by loss of selective neurons in discreet part of the brain. The peptide angiotensin II (Ang II) plays significant role in hippocampal and striatal neurons degeneration through the generation of reactive oxygen species. Blockade of the angiotensin converting enzyme or ATI receptors provides protection in animal models of neurodegenerative diseases. In the present study, the neuroprotective effect of captopril was investigated in Drosophila melanogaster model using the UAS-GAL4 system to express the synuclein and Aβ42 peptide in the flies’ neurons.Methods: The disease causing human Aβ42 peptide or α-syn was expressed pan-neuronally (elav-GAL4) or dopamine neuron (DDC-GAL4) using the UAS-GAL4 system. Flies were either grown in food media with or without captopril (1, 5, or 10µM). This was followed by fecundity, larva motility, negative geotaxis assay (climbing) and lifespan as a measure of neurodegeneration.Results: Elav-Gal4